Privacy enhancement using selective encryption scheme in data outsourcing - Long Nguyen-Vu; Jungsoo Park; Minho Park; Souhwan Jung (International Journal of Distributed Sensor Networks)
In this article, we introduce a practical scheme that dynamically secures and outsources data on demand as well as propose a corresponding architecture to securely process data in database service provider. We also adopt the application of bring your own device in this scheme as an enhanced security solution. After studying over 1300 database models, we expect this scheme can be applied in production with justifiable result.